Greenhouse Gas Accounting for Sustainable Land Management : Quick Guidance for Users - Toudert, Anass; Braimoh, Ademola; Bernoux, Martial; St-Louis, Maylina; Abdelmagied, Manar; Bockel, Louis; Ignaciuk, Adriana; Zhao, Yuxuan (World Bank, Washington, DC, 2018)
Agriculture, and the patterns of land use change that are associated with it, have a high environmental footprint and contribute to climate change, as the sector accounts for about one-quarter of anthropogenic greenhouse gas (GHG) emissions globally. However, improved land management practices can play an important role in mitigating GHG emissions by removing substantial volumes of carbon from the atmosphere and sequestering them in soils and plant tissues. We can’t fix what we do not measure, which is why quantifying greenhouse gas emissions is a necessary step for climate-smart agriculture and sustainable land management. Greenhouse gas accounting can provide the numbers and data that are important to decision making in adopting less carbon-intensive practices and guiding low-emissions development